36a Biennale internazionale d'arte. - 36a Biennale di Venezia, 1972 (Venezia : La Biennale di Venezia, 1972)
Acconci, Vito ; Baldessari, John ; Vautier, Ben ; Beuys, Joseph ; Boetti, Alighiero ; Boltanksy, Christian ; Brown, Trisha ; Buren, Daniel ; Calzolari, Pierpaolo ; Chiari, Giuseppe ; De Dominicis, Gino ; De Maria, Walter ; Fabro, Luciano ; Fox, Terry ; Gilbert & George ; Graham, Dan ; Kounellis, Jannis ; La Monte Young ; Merz, Mario & Marisa ; Moorman, Charlotte ; Nauman, Bruce ; Ono, Yoko ; Oppenheim, Dennis ; Palermo, Blinky ; Paolini, Giulio ; Paxton, Steve ; Pisani, Vetto ; Pistoletto, Michelangelo ; Prini, Emilio ; Rinke, Klaus ; Warhol, Andy ; etc.
36a Biennale internazionale d'arte, Venezia, 1972
Italiaans
kunstcatalogus